2022 KLEIN LECTURE PARENTAL EDUCATION AND INVENTION: THE FINNISH ENIGMA. (21st March 2023) - Aghion, Philippe; Akcigit, Ufuk; Hyytinen, Ari; Toivanen, Otto
Abstract: Why is invention strongly positively correlated with parental income not only in the United States but also in Finland, which displays low income inequality and high social mobility? Using data on 1.45 M Finnish individuals and their parents, we find the following: (i) the positive association between parental income and off‐spring probability of inventing is greatly reduced when controlling for parental education; (ii) instrumenting for the parents having an MSc degree using distance to nearest university reveals a large causal effect of parental education on offspring probability of inventing; and (iii) the causal effect of parental education has been markedly weakened by the introduction in the early 1970s of a comprehensive schooling reform.